PENERAPAN METODE SAS (STRUKTURAL ANALITIK SINTETIK) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS I SDN 88 PEKANBARU - Indrianty, Dwi; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: SAS method (Structural Analytical Synthetic) in beginning reading skill improvement in I Grade Primary School. This research aim to describe: a step-by-step method of SAS (Structural Analytical Synthetic) that can improve beginning reading and improved reading skills beginning first grade elementary school students. This research uses classroom action research conducted in two cycles, each cycle includes the planning, implementation, observation and reflection. The results include: the use of measures SAS method can work well and improve the I grade read the beginning of elementary school. Background problem in this research is the low reading skills of students who do not reach KKM (Minimum Completeness Criteria) established by the school which is 72 to 21 the number of students who do not reach KKM 11 students (52.3%) and who completed 9 students (42, 8%). Based on the problem, the researchers conducted a PTK using SAS. In using this method, the quality of the learning process has increased. Based on data from this study can be seen from the observation of student activity in the first cycle with a percentage of 60% the first meeting enough categories, 75% meeting II both categories increased in the second cycle to 80% in the first meeting either category, and 95% meeting II category very well. Activities of teachers also increased from 75% in both categories dipertemuan I, 80% II meeting both categories in the first cycle and to 85% with very good category at the first meeting and 90% II meeting with the category very well in the second cycle. Preliminary data as the basis of a score of 21 students averaged 67.07, and the first cycle increased to 68.72 (2.46%), on the second cycle increased to 80.80 (20.47%). From the above data it can be concluded by applying SAS can improve the results of the reading skills of students of class I SDN 88 Pekanbaru. Keywords: beggining reading skill. SAS method